La ruine angkorienne et le fromager : une mise en cloche d’un paysage fantasmé synonyme d’inaction ? - Sébastien Preuil (Projets de Paysage)
From the rice paddies to the major urban centres, images of landscapes in the tropics circulating today take on a variety of forms. Although most of these representations correspond to reality, some are more of the realm of fantasy or come from another era, as in the case of the representation of the ancient city reclaimed by the jungle. This is the image we have of the Khmer temples in Cambodia. In the specific case of Angkor, the architectural jewel of Khmer civilization, certain representations of landscapes forged during the colonial era, and which are now relayed by the media and social networks, have repercussions on the way certain temples are managed. Today, although most Khmers do not appreciate this image of temples reclaimed by the forest which they consider as disrespectful of deities and a sign of the decline of their civilization, some monuments are voluntarily maintained by the Apsara Authority in a state of ruin in order to perpetuate romantic images which appeal to foreign tourists. But is such a form of conservation tantamount to inaction? This study was carried out in 2010 and 2011 for our thesis, as part of our research on heritagisation and simulacrum in Angkor. We used quantitative interviews to study people’s relationship to ruins depending on whether they are foreign tourists or Khmer visitors.